Pembrolizumab monotherapy in patients with previously treated metastatic high-grade neuroendocrine neoplasms: joint analysis of two prospective, non-randomised trials - Vijayvergia, Namrata; Dasari, Arvind; Deng, Mengying; Litwin, Samuel; Al-Toubah, Taymeyah; Alpaugh, R. Katherine; Dotan, Efrat; Hall, Michael J.; Ross, Nicole M.; Runyen, Melissa M.; Denlinger, Crystal S.; Halperin, Daniel M.; et al. (British journal of cancer, 2020)
Background Metastatic high-grade neuroendocrine neoplasms (G3NENs) have limited treatment options after progression on platinum-based therapy. We addressed the role of Pembrolizumab in patients with previously treated metastatic G3NENs. Methods Two open-label, phase 2 studies enrolled patients with G3NEN (Ki-67 > 20%) to receive Pembrolizumab at 200 mg I.V. every 3 weeks. Radiographic evaluation was conducted every 9 weeks with overall response rate as the primary endpoint. Results Between November 2016 and May 2018, 29 patients (13 males/16 females) with G3NENs were enrolled. One patient (3.4%) had an objective response and an additional six patients (20.7%) had stable disease, resulting in a disease control rate of 24.1%. Disease control rate (DCR) at 18 weeks was 10.3% (3/29). There was no difference in the DCR, PFS or OS between the PD-L1-negative and -positive groups ( p 0.56, 0.88 and 0.55, respectively). Pembrolizumab was well tolerated with only 9 grade 3, and no grade 4 events considered drug-related. Conclusions Pembrolizumab can be safely administered to patients with G3NENs but has limited activity as a single agent. Successful completion of our trials suggest studies in G3NENs are feasible and present an unmet need. Further research to identify active combination therapies should be considered. Clinical trial registration number NCT02939651 (10/20/2016).